Phenology and distribution of Greenland White-fronted Geese Anser albifrons flavirostris staging in Iceland - Fox, A D; Hilmarsson, J O; Einarsson, O; Boyd, H; Kristiansen, J N; Stroud, D A; Walsh, A J; Warren, S M; Mitchell, C; Francis, I S; Nygård, T (Wildfowl, 1999)
A combination of ringing recoveries, resightings of individually marked birds and regularly counted census routes suggest that Greenland White-fronted Geese stage in Iceland from c.10 April until c.12 May in spring and c.30 August until c.31 October in autumn. Observations confirm that there are two main areas used by the population, the southern lowlands (Arnessysla, Rangrvallassysla and Vestur-Skaftafellssysla) and the western lowlands (Kjsarsysla, Borgarfjardarsysla, Myrarsysla and Snaefellsness- og Hnappadalssysla) which are exploited in both spring and autumn. Spring migration phenology appears to differ between areas, with earlier arrivals in the southern lowlands where numbers peaked during 24-26 April in 1990-1992, compared to a rapid build up in western staging areas to peak numbers during 18-22 April in 1997-1999, where substantial numbers of birds remained well into May each year. These differences most likely relate to the timing of migration in the years concerned, but could also reflect different migration strategies of birds using the two areas (records of individuals using both staging areas are rare). At the most important staging site in the western lowlands, Hvanneyri, up to a maximum of 1500 birds were counted. Based on observations of individually marked birds at Hvanneyri, more than half of the geese remained for less than a week, mostly early on in migration, whilst more than a third stayed for almost the entire staging period (c. 24 days). More detailed information relating tot he behaviour of individuals is required to fully understand the importance of the staging periods in Iceland to this goose population.